Participation, Decentralization and Human Rights : A Review of Approaches for Strengthening Voice and Accountability in Local Governance - Friis-Hansen, Esbern (World Bank, Washington, DC, 2017)
This report examines the theoretical and practical synergies between three intervention models that are currently being employed to improve local governance in developing countries: 1) democratic decentralization or devolution; 2) community participatory approaches, and; 3) rights-based approaches. The aim is to identify the possibilities and challenges of an 'integrative approach' to local governance that combines the strengths of each of the three intervention models. It is assumed that an integrative approach can help enhance efforts to improve the downward accountability of local governments, enhance equity in the distribution of services and in various citizens' access to influence, and increase citizen participation in local governance processes. This is supported by a number of empirical cases from Africa, Latin America, Asia and Bosnia-Herzegovina, which are presented in the report. Each case also highlights a number of context-specific challenges to using an integrative approach, such as available financial resources, national policy environments and local conflicts. The report fills this gap by both identifying theoretical synergies and by drawing on the few empirical cases that exist.